Improvement of technical performance of heat regenerator of GPU-3 Stirling engine - Mohammad Sheykhi; Mahmood Mehregan (Energy Reports, 2023)
In this paper, in order of simulate the performance of Stirling engine a novel adiabatic model (irreversible adiabatic) is proposed for the Ground Power Unit Stirling engine, which has higher accuracy than previous models of this Stirling engine. Then the effects of important parameters of Stirling engine such as regenerator length, regenerator porosity, engine rotational speed, and pressure on the performance of the Ground Power Unit engine are investigated and optimal conditions of these parameters are provided for three different operating pressures. The engine modeling is conducted by the Runge–Kutta method and the genetic algorithm technique is used to optimize the engine. The results show that the power output and thermal efficiency of model are in good agreement with the experimental data. Also, at high rotational speeds, by increasing the regenerator length, the pressure drop increases and the power output decreases sharply; therefore, it is better to use short regenerators to achieve proper thermal efficiency. Also, at high rotational speeds and low regenerator porosity, the pressure drop of regenerator increases so much that at 3500 rpm and 0.65 porosity, the pressure drop reaches more than 2.5 bar. For maximize the power and thermal efficiency, a high porosity coefficient is recommended at high rotational speeds.